Biologia reprodutiva e desenvolvimento dos filhotes de cágado amarelo Acanthochelys radiolata (Mikan, 1820) em cativeiro (Reptilia: Testudines: Chelidae) - Mocelin, Márcia (2001)
To determine the mating period, posture, egg incubation and hatchling of the young of Acanthochelys radiolata, six males and ten females from several regions of the State of Rio de Janeiro were observed in a stand at the Fundação Jardim Zoológico da Cidade do Rio de Janeiro (RIOZOO). Daily observations, 15 minutes each, were made with the ad libitum method to characterise the mating behaviour. Four mates were observed between the months of November and March. The stand was daily examined to check the possibility of egg postures. Fifteen egg postures were found between the months of March and July, with an isolated posture in November and another in January. These eggs resulted in one hatchling. Fourteen eggs were found in the nature, from which three turtles were born. These eggs were less massive than those obtained in captivity. The hatchling occurred between September and November. Two young were followed for a year to determine the growth rate and the ontogenetic colour variation. The turtles were born with red marks over a black background that changed to yellow marks after three months. The mating behaviour of the turtles was distinct to those found in other studies of similar species in captivity, but comparable to field observations reported elsewhere.